KAJIAN KERUSAKAN LINGKUNGAN PERAIRAN AKIBAT AKTIVITAS PENAMBANGAN TIMAH PUTIH (Sn) DI SEKITAR SUNGAI JELITIK KABUPATEN BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG - , BINTORO SAPUTRO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to determine the effect of tin mining (Sn) for environmental damage at Jelitik river that indicated by the decline in river water quality and damage to riparian Jelitik river. This research method is a survey with a sample taken by purposive sampling of river water at the upstream, midstream, and downstream river Jelitik and wastewater of tin mining activities before going into the waters of the River, with parameters include turbidity, pH, heavy metals that is iron (Fe ), Zinc (Zn), Copper (Cu), Lead (Pb) and Cadmium (Cd). For turbidity, and pH measurements were made directly using a water quality chekeer. Based on the results of laboratory analysis of water quality showed that 4 Jelitik River water quality parameters measured has exceeded the required quality standards in accordance with the PPRI Number 82 Year 2001 and Permenkes Number 416 of 1990 on terms and Water Quality Monitoring pH value is an average 5.39, metal Iron (Fe) in the river upstream (P1) 0.053 mg/l, central (P2) 0.458 mg/l, and Lower (P4) 0.380 mg/l with standard quality 0 mg/l and turbidity in the middle (P2) and Downstream (P4) > 999 NTU to 25 NTU environmental standards as well as the downstream river Zn metal (P4) 0.082 mg/l to the environmental quality standard of 0.05 mg/l. This means that water quality of Jelitik River has declined due to mining activities that rivers. Mining activities also affect to border of river in the middle and lower with area 1,983 acres in the middle and 1,663 acres in the lower.